2020
DOI: 10.4049/jimmunol.1900543
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Cancer Cells Induce the Release of Mitochondrial Extracellular DNA Traps by Viable Neutrophils

Abstract: Neutrophils are key effector cells that orchestrate inflammatory responses in the tumor microenvironment. Although neutrophil extracellular DNA traps (NETs) entrap and kill pathogens, they also contribute to chronic inflammation and cancer progression. Thyroid cancer (TC) is the most frequently occurring cancer of the endocrine system, accounting for 70% of deaths due to endocrine tumors. Although anaplastic TC (ATC) is rare among TCs, it is highly lethal. We demonstrated in a recent study that tumor-infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 72 publications
0
65
1
Order By: Relevance
“…The conversion to a mucoid phenotype coincided with a decline in susceptibility to NETs, raising the possibility that increased alginate production decreases interactions with NETs, or otherwise interferes with killing by NET-associated granule proteins 48 . 4,6,7,144,152 . If the source of infection/stimulation persists, the released mtDNA, having similarity to viral and bacterial DNA (enriched in unmethylated CpG motifs), acts as a danger signal and triggers cytokine production for a protective and regulated immune response 7,55 .…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion to a mucoid phenotype coincided with a decline in susceptibility to NETs, raising the possibility that increased alginate production decreases interactions with NETs, or otherwise interferes with killing by NET-associated granule proteins 48 . 4,6,7,144,152 . If the source of infection/stimulation persists, the released mtDNA, having similarity to viral and bacterial DNA (enriched in unmethylated CpG motifs), acts as a danger signal and triggers cytokine production for a protective and regulated immune response 7,55 .…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 99%
“…More recently, it was reported that anaplastic thyroid cancer (ATC) cells induce the release of mitochondrial extracellular DNA traps by viable neutrophils. ATC conditioned medium (CM)-primed neutrophils promoted ATC cell proliferation in a NET-dependent manner 144 . Furthermore, tumor cells have been demonstrated to produce IL-8, attracting myeloid-derived suppressor cells (MDSC) and activating granulocytic MDSC to extrude DNA nets 145 .…”
Section: The Formation Of Extracellular Dna Traps In Cancermentioning
confidence: 99%
“…1 In the last decades this view has been challenged due to recent evidences indicating that neutrophils survival time is significantly longer than the lifespan usually reported (<1 d) 2 and they produce a variety of cytokines and chemokines, 3 lipid mediators, angiogenic factors, 4 and neutrophil extracellular traps. 5 There is now evidence that PMNs play a role in several chronic inflammatory disorders, 6 cardiovascular diseases, 7 asthma, 8,9 tumors, 4,10 sepsis, 11,12 and parasitic diseases. 13 To exert their functions, PMNs express a plethora of immunoreceptors, including TLRs 14 and endocannabinoids receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils from patients with myeloproliferative neoplasms associated with JAK2 V617F somatic mutation have an increase in NET formation and thrombosis and mice with knock-in of JAK2 V617F have an increased propensity for NET formation and thrombosis (166). Recently, we have demonstrated that anaplastic thyroid cancer cells can induce the release of mitochondrial DNA traps by viable neutrophils (167). Collectively, these studies indicate that NETs can sustain several aspects of tumor growth, the formation of metastasis, and promote cancer-associated thrombosis.…”
Section: Formation Of Extracellular Dna Traps By Basophilsmentioning
confidence: 99%
“…Activated human and mouse basophils release BETs ( 116 118 ). There is mounting evidence that extracellular DNA traps have multiple effects in cancer ( 160 ) favoring tumor growth ( 167 ), awakening dormant cancer cells ( 165 ), and promoting metastasis in mouse models and in humans ( 161 , 164 ). Further studies should evaluate the presence of BETs in experimental and human cancers and whether basophil extracellular traps modulate tumor growth and the formation of metastasis in vivo .…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 99%